The Use of Flash Card Media to Improve Recognition of Numbers 1-10 in Children with Mild Mental Retardation: A Case Study at SLB N X Kudus - Elrika, Anastasia Jevis; Rahmadhani, Renita Mila; Ruby, Arcivid Chorynia (Jurnal Prajaiswara, 2025)
Introduction/Main Objectives: This study aims to analyze the process and impact of using flash card media to improve number recognition skills (1–10) among students with mild intellectual disabilities in class 5C at SLB Negeri X Kudus. Research Methods: The research employed a qualitative method with a case study approach, focusing on a student identified as SR who had difficulties in recognizing numerical symbols and arranging them sequentially. Data were collected through interviews, observation, and documentation over four learning sessions using flash card media. Finding/Results: The results revealed a significant improvement in three main indicators: number pronunciation, matching numbers with pictures, and sequencing numbers correctly. Additionally, improvements were noted in the student's motor coordination and emotional responses. These findings are supported by the dual coding and active recall theories, which are relevant for special needs learners with visual and kinesthetic learning styles. The study concludes that flash cards are an effective and enjoyable strategy for teaching numeracy to students with intellectual disabilities. Conclusion: This research offers practical implications for special education teachers in designing visually engaging and adaptive learning strategies tailored to student needs. The results of this study provide practical contributions for special education teachers in selecting enjoyable visual media-based numeracy strategies.